Implementing an intervention to improve decision making around referral and admission to intensive care: Results of feasibility testing in three NHS hospitals. Issue 1 (17th May 2019) - Rees, Sophie; Bassford, Christopher; Dale, Jeremy; Fritz, Zoe; Griffiths, Frances; Parsons, Helen; Perkins, Gavin D.; Slowther, Anne Marie
Abstract: Rationale, aims, and objectives: Decisions about whether to refer or admit a patient to an intensive care unit (ICU) are clinically, organizationally, and ethically challenging. Many explicit and implicit factors influence these decisions, and there is substantial variability in how they are made, leading to concerns about access to appropriate treatment for critically ill patients. There is currently no guidance to support doctors making these decisions. We developed an intervention with the aim of supporting doctors to make more transparent, consistent, patient‐centred, and ethically justified decisions. This paper reports on the implementation of the intervention at three NHS hospitals in England and evaluates its feasibility in terms of usage, acceptability, and perceived impact on decision making. Methods: A mixed method study including quantitative assessment of usage and qualitative interviews. Results: There was moderate uptake of the framework (28.2% of referrals to ICU across all sites during the 3‐month study period). Organizational structure and culture affected implementation. Concerns about increased workload in the context of limited resources were obstacles to its use. Doctors who used it reported a positive impact on decision making, with better articulation and communication of reasons for decisions, and greater attention to patient wishes. The intervention made explicit the uncertainty inherent in these decisions, and this was sometimes challenging. The patient and family information leaflets were not used. Conclusions: While it is feasible to implement an intervention to improve decision making around referral and admission to ICU, embedding the intervention into existing organizational culture and practice would likely increase adoption. The doctor‐facing elements of the intervention were generally acceptable and were perceived as making ICU decision making more transparent and patient‐centred. While there remained difficulties in articulating the clinical reasoning behind some decisions, the intervention offers an important step towards establishing a more clinically and ethically sound approach to ICU admission.